IMPLEMENTASI LEARNING LEADERSHIP KEPALA SEKOLAH BERBASIS COACHING UNTUK PENGEMBANGAN KINERJA GURU SEKOLAH DASAR STUDY KUALITATIF DESKRIPTIF PADA SDN PAMEUNGPEUK 3 - Nur Endah Sariningsih; Sri Handayani; Eva Dianawati Wasliman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the implementation of the principal's learning leadership based on coaching in improving teacher performance at SDN Pameungpeuk 03, Bandung Regency. The focus of the research includes three main dimensions: defining the school mission, managing the instructional program, and promoting a positive school learning climate. Using a descriptive qualitative approach with a case study method, data were collected through in-depth interviews, participant observation, and documentation studies involving the principal and teachers. Data validity was ensured through source and technique triangulation. The results showed that the principal successfully transformed into a learning leader through the implementation of the GROW (Goal, Reality, Options, Will) coaching model. The dimension of defining the mission was carried out participatively, ensuring that the school's vision was internalized as a shared value. In instructional management, the supervision paradigm shifted from inspection to reality-based reflective assistance. A positive learning climate was created through an appreciation culture and professional learning communities that increased teacher self-efficacy. The innovation offered is the systemic integration of Hallinger’s framework and Knight’s coaching techniques to overcome digital competence gaps and infrastructure limitations. This study concludes that coaching-based learning leadership is an effective catalyst for sustainable teacher performance development in primary schools.